2000
DOI: 10.1021/bc0000583
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyamidoamine Dendrimers Having Poly(ethylene glycol) Grafts and Their Ability To Encapsulate Anticancer Drugs

Abstract: Polyamidoamine dendrimers having poly(ethylene glycol) grafts were designed as a novel drug carrier which possesses an interior for the encapsulation of drugs and a biocompatible surface. Poly(ethylene glycol) monomethyl ether with the average molecular weight of 550 or 2000 was combined to essentially every chain end of the dendrimer of the third or fourth generation via urethane bond. The poly(ethylene glycol)-attached dendrimers encapsulating anticancer drugs, adriamycin and methotrexate, were prepared by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
532
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 632 publications
(554 citation statements)
references
References 36 publications
18
532
1
3
Order By: Relevance
“…Complete release of efavirenz within first 24 h from drug containing polypropylenimine (PPI) dendrimers while significantly slower release from t-Boc glycine conjugated and mannose conjugated PPI dendrimers was reported by Dutta et al (24). Drug release was also found to be controlled by molecular architecture (25) of dendrimer and introducing poly(ethylene oxide) chains on the periphery of the dendrimer (26,27). These observations suggest that further studies need to be conducted to avoid the premature release as well as control the release of SN-38 from the complexes.…”
Section: Drug Releasementioning
confidence: 83%
“…Complete release of efavirenz within first 24 h from drug containing polypropylenimine (PPI) dendrimers while significantly slower release from t-Boc glycine conjugated and mannose conjugated PPI dendrimers was reported by Dutta et al (24). Drug release was also found to be controlled by molecular architecture (25) of dendrimer and introducing poly(ethylene oxide) chains on the periphery of the dendrimer (26,27). These observations suggest that further studies need to be conducted to avoid the premature release as well as control the release of SN-38 from the complexes.…”
Section: Drug Releasementioning
confidence: 83%
“…We have shown that PEG chains can be attached to all chain ends of PAMAM G3 and G4 dendrimers by the reaction of amine-terminated dendrimers and methoxy-PEG-4-nitrophenyl carbonate (Figure 1). 11 Dendrimers of various types are shown to be capable of encapsulating small guest molecules. Indeed, PAMAM dendrimers can encapsulate various molecules.…”
Section: Poly(ethylene Glycol)-modified Dendrimers As Nanocontainers mentioning
confidence: 99%
“…As shown in Table 1, the dendrimers of higher generation with longer PEG chains exhibited higher encapsulation ability for both drugs, most likely because of the space created by their larger dendrimer interior and the larger hydration layers formed by PEG chains. 11 In addition, PEG-modified PAMAM dendrimers exhibited higher encapsulation ability toward methotrexate, which has two carboxyl groups in the molecule, compared with doxorubicin. Their drug-release behaviors were also examined.…”
Section: Poly(ethylene Glycol)-modified Dendrimers As Nanocontainers mentioning
confidence: 99%
“…Dendrimers (Scheme 1) are also unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with strong affinity towards DNA and RNA complexation [4][5][6][7][8][9][10]. It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%